Explosion-proof assembly based on ceramic and mechanical superstructure material

By combining boron carbide ceramics, SC+FCC mechanical superstructure materials and ultra-high molecular weight polyethylene fiber composite materials, the problems of heavy weight of explosion-proof components and poor vehicle passability are solved, achieving lightweight and efficient energy absorption and strong protection, and improving the vehicle's protection against explosion shock waves and fragments.

CN120740376AActive Publication Date: 2025-10-03INNER MONGOLIA METAL MATERIAL RES INST
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511159461.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-10-03
Estimated Expiration
2045-08-19

AI Technical Summary

Technical Problem

Existing explosion-proof components are heavy, affecting the vehicle's maneuverability and passability, and traditional structural designs reduce the vehicle's passability and off-road capabilities.

Method used

It adopts boron carbide ceramic crushing energy absorption layer, SC+FCC mechanical superstructure material support energy absorption layer and ultra-high molecular weight polyethylene fiber composite material fragment protection layer, and realizes lightweight, efficient energy absorption and strong protection through the synergistic mechanism of reflection, deformation and interception.

Benefits of technology

Without sacrificing the vehicle's passability and maneuverability, the vehicle's weight is significantly reduced, the protection against explosion shock waves and fragments is improved, and the vehicle's ability to break away is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120740376A_ABST
    Figure CN120740376A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of armor protection, in particular to an anti-explosion assembly based on ceramic and mechanical super-structure materials, which comprises a breaking energy absorption layer, an anti-explosion layer and a protective layer, and is characterized in that the breaking energy absorption layer is made of boron carbide ceramic and is used for reflecting and refracting refracted waves of an explosion facing surface and dissipating impact energy; the supporting energy absorption layer absorbs impact energy refracted by the ceramic through self-deformation energy absorption; and the fragment protection layer is made of an ultra-high molecular weight polyethylene fiber composite material and is used for intercepting ceramic fragments of the crushing energy absorption layer and fragments of the supporting energy absorption layer. Through a three-layer cooperation mechanism of the breaking energy absorption layer, the supporting energy absorption layer and the fragment protection layer, multi-stage attenuation is achieved on explosive shock waves. Meanwhile, after explosion, the assembly is separated from the vehicle body through breaking, the additional weight of the vehicle body is reduced, and the capability of getting rid of dangerous areas after the vehicle attacks is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of armor protection, and in particular to an explosion-proof component based on ceramic and mechanical superstructure materials. Background Art

[0002] In the context of great power competition, modern warfare is characterized by asymmetric tactics, with the weaker side relying primarily on mines, improvised explosive devices, and other devices to deplete the superior side. This is particularly true in urban warfare, where mine-class improvised explosive devices are more concealed. Improving the blast resistance of tactical vehicles has become a major focus for various countries. For mine-resistant ambush-protected vehicles, which serve as frontline assault vehicles, enhanced blast resistance is particularly important. Currently, blast protection methods for mine-resistant ambush-protected vehicles fall into two main categories: one employs specialized structural designs, such as a V-shaped hull, but this requires a large installation space, significantly reducing the vehicle's maneuverability and off-road capability. The other involves the addition of mine protection components. Traditional components often utilize a "armored steel + foam aluminum" structure, which, while providing some protection, is excessively heavy and significantly impacts vehicle maneuverability.

[0003] In response to the above problems, there is an urgent need to develop a lightweight and efficient explosion-proof component that can improve the protection against explosion shock waves and fragments without sacrificing the vehicle's passability and maneuverability, and meet the actual combat needs of equipment such as mine-resistant ambush-proof vehicles. Summary of the Invention

[0004] In response to the shortcomings of the existing technology, the present invention provides an explosion-proof component based on ceramics and mechanical superstructure materials, which solves the problems of the existing explosion-proof components being heavy and affecting vehicle maneuverability, and the special vehicle body structure reducing passability, achieving the synergistic effect of "lightweight, efficient energy absorption, and strong protection", while ensuring the passability of tactical vehicles and the ability to escape after an attack.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: an explosion-proof component based on ceramic and mechanical superstructure materials, comprising: The energy-absorbing layer is made of boron carbide ceramic. Its function is to first reflect a portion of the detonation shock wave through the blast surface during an explosion. It then shatters under the action of the high-intensity shock wave, utilizing the complex interface effect formed after the shattering to reflect and refract the refracted wave multiple times, significantly dissipating the impact energy. The energy-absorbing layer is produced using a compression molding and vacuum sintering process. Boron carbide powder is mixed with sintering aids such as silicon powder and carbon powder, then pressed and sintered to produce a ceramic sheet. The supporting energy-absorbing layer is made of SC+FCC mechanical superstructure material, a porous titanium alloy material produced by selective laser melting and sintering. It is used to support the crushing energy-absorbing layer and further absorb the impact energy after the ceramic layer is refracted through its own deformation; The debris protection layer is an ultra-high molecular weight polyethylene fiber composite material, which is used to intercept ceramic fragments generated by the broken energy-absorbing layer and structural fragments supporting the energy-absorbing layer, preventing the fragments from penetrating the vehicle body and causing damage; the fiber cloth is made of plain weave and is cured after being impregnated with epoxy resin.

[0006] Preferably, the preparation method of the supporting energy absorbing layer is as follows: S1. Raw material preparation Prepare a raw material containing 90% titanium, 6% aluminum, and 4% vanadium by weight, and prepare the raw material into a titanium alloy powder, wherein the particle size of the titanium alloy powder is 15-53 μm; S2. Powder laying The pre-treated titanium alloy powder is laid on the workbench of the selective laser melting and sintering equipment. The laying thickness is controlled at 50-100μm to ensure a uniform powder layer and avoid local accumulation or vacancies. S3. Laser Melting and Sintering Use a high-power fiber laser to scan and sinter the laid powder layer. The laser selectively melts according to the preset mechanical superstructure model path, so that the powder particles fuse together to form a solid structural layer. S4. Layer by layer After one layer is sintered, the workbench descends to a height corresponding to the set layer thickness, which is consistent with the laying thickness. Then, the powder spreading device again evenly spreads the titanium alloy powder on the surface of the sintered structural layer, repeating the laser melting and sintering process in step 4. This cycle is repeated to gradually accumulate and form a complete SC+FCC mechanical superstructure material blank. S5. Post-processing The unsintered powder attached to the surface of the material body is removed by high-pressure air blowing and vibration screening. The material body is annealed to eliminate internal stress at a temperature of 600-800°C and a holding time of 1-2 hours. Finally, the material is precisely processed in shape and size to obtain a supporting energy-absorbing layer.

[0007] Preferably, the method for preparing the explosion-proof component comprises the following steps: S1.Surface treatment The bottom surface of the crushing energy absorbing layer, the upper and lower surfaces of the supporting energy absorbing layer, and the top surface of the debris protection layer are sandblasted to remove the surface oxide layer and impurities, and the roughness is controlled at Ra1.6-3.2μm; S2. Gluing and lamination Evenly coat the upper surface of the supporting energy-absorbing layer with epoxy resin adhesive to a thickness of 0.2-0.5 mm, align the bottom surface of the crushed energy-absorbing layer with the upper surface of the supporting energy-absorbing layer, apply a pressure of 5-10 MPa, and preliminarily cure at room temperature for 1-2 hours; S3. Secondary gluing and lamination Coat the lower surface of the supporting energy-absorbing layer with the same adhesive to a thickness of 0.2-0.5 mm, align the top surface of the debris protection layer with the lower surface of the supporting energy-absorbing layer, apply a pressure of 5-10 MPa, and cure at 60-80°C for 4-6 hours to obtain a complete explosion-proof assembly.

[0008] Preferably, the titanium alloy powder is dried and sieved before being laid to remove impurities and agglomerated particles.

[0009] Preferably, the laser power of the laser melting is 100-200 W, and the scanning speed is 500-1000 mm / s.

[0010] The present invention provides an explosion-proof component based on ceramic and mechanical superstructure materials. It has the following beneficial effects: This invention utilizes boron carbide ceramics (2.5g / cm³), SC+FCC mechanical superstructure materials (1.5005g / cm³), and ultra-high molecular weight polyethylene composite materials (1.0g / cm³). The overall density is far lower than that of traditional armored steel (7.85g / cm³), significantly reducing vehicle weight and improving maneuverability. Through a three-layer synergistic mechanism of "ceramic reflection, superstructure deformation, and fragment interception," it achieves multi-stage attenuation of explosion shock waves. Furthermore, after the explosion, components shatter and disintegrate, freeing them from the vehicle body. This reduces added weight and improves the vehicle's ability to escape danger zones after an attack. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is a schematic structural diagram of the explosion-proof assembly of the present invention; Figure 2 This is a schematic diagram of the detonation proof test device of the present invention; Figure 3 Schematic diagram of the original cell structure of the SC+FCC mechanical superstructure material of the present invention; Figure 4 This is a detonation pressure curve diagram of the ceramic explosion surface of the present invention; Figure 5 is the detonation pressure curve of the back side of the ultra-high molecular weight polyethylene fiber composite material plate of the present invention; Figure 6 This is a physical picture of the front blast surface and back blast surface of the armor steel after the test of the present invention, where a is the detonation surface and b is the back blast surface.

[0012] Among them, 1. Crushing energy absorbing layer; 2. Supporting energy absorbing layer; 3. Debris protection layer. DETAILED DESCRIPTION

[0013] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention. Example 1

[0014] An embodiment of the present invention provides an explosion-proof component based on ceramic and mechanical superstructure materials, comprising: The crushing energy absorbing layer 1 is made of boron carbide ceramics, which is used to reflect and refract the refracted waves from the explosion surface to dissipate the impact energy; The supporting energy absorbing layer 2 absorbs the impact energy after the ceramic is refracted by the supporting energy absorbing layer 2 through its own deformation; The fragment protection layer 3 is an ultra-high molecular weight polyethylene fiber composite material, which is used to intercept ceramic fragments that break the energy absorbing layer 1 and fragments that support the energy absorbing layer 2.

[0015] The preparation method of the supporting energy absorbing layer 2 is as follows: S1. Raw material preparation Prepare raw materials with 90% titanium, 6% aluminum, and 4% vanadium by weight, and make them into titanium alloy powder. The particle size of the titanium alloy powder is 53 μm. Before laying the titanium alloy powder, the titanium alloy powder is dried and sieved to remove impurities and agglomerated particles. S2. Powder laying The pre-treated titanium alloy powder is laid on the workbench of the selective laser melting and sintering equipment. The laying thickness is controlled at 100 μm to ensure a uniform powder layer and avoid local accumulation or gaps. S3. Laser Melting and Sintering A high-power fiber laser is used to scan and sinter the laid powder layer. The laser power is 200W and the scanning speed is 1000mm / s. The laser selectively melts according to the preset mechanical superstructure model path, so that the powder particles fuse with each other to form a solid structural layer. S4. Layer by layer After one layer is sintered, the workbench descends to a height that matches the set layer thickness. The powder spreading device then evenly spreads the titanium alloy powder on the surface of the sintered structural layer, repeating the laser melting and sintering process in step 4. This cycle repeats until a complete SC+FCC mechanical superstructure material body is gradually formed. S5. Post-processing The unsintered powder attached to the surface of the material body is removed by high-pressure air blowing and vibration screening. The material body is annealed to eliminate internal stress at an annealing temperature of 800°C and a holding time of 2 hours. Finally, the material is precisely processed in shape and size to obtain the support energy-absorbing layer 2.

[0016] The method for preparing an explosion-proof component comprises the following steps: S1.Surface treatment The bottom surface of the crushing energy absorbing layer 1, the upper and lower surfaces of the supporting energy absorbing layer 2, and the top surface of the debris protection layer 3 are sandblasted to remove the surface oxide layer and impurities, and the roughness is controlled at Ra3.2μm; S2. Gluing and lamination Evenly coat the upper surface of the supporting energy absorbing layer 2 with epoxy resin adhesive to a thickness of 0.5 mm, align the bottom surface of the crushing energy absorbing layer 1 with the upper surface of the supporting energy absorbing layer 2, apply a pressure of 10 MPa, and preliminarily cure at room temperature for 2 hours; S3. Secondary gluing and lamination The same adhesive is applied to the lower surface of the supporting energy absorbing layer 2 with a thickness of 0.5 mm. The top surface of the debris protection layer 3 is aligned with the lower surface of the supporting energy absorbing layer 2, and a pressure of 10 MPa is applied. The mixture is cured at 80°C for 6 hours to obtain a complete explosion-proof assembly. The structure of the explosion-proof assembly is shown in the figure below. Figure 1 shown. Example 2

[0017] An embodiment of the present invention provides an explosion-proof component based on ceramic and mechanical superstructure materials, comprising: The crushing energy absorbing layer 1 is made of boron carbide ceramics, which is used to reflect and refract the refracted waves from the explosion surface to dissipate the impact energy; The supporting energy absorbing layer 2 absorbs the impact energy after the ceramic is refracted by the supporting energy absorbing layer 2 through its own deformation; The fragment protection layer 3 is an ultra-high molecular weight polyethylene fiber composite material, which is used to intercept ceramic fragments that break the energy absorbing layer 1 and fragments that support the energy absorbing layer 2.

[0018] The preparation method of the supporting energy absorbing layer 2 is as follows: S1. Raw material preparation Prepare raw materials containing 90% titanium, 6% aluminum, and 4% vanadium by weight, and make them into titanium alloy powder. The particle size of the titanium alloy powder is 15 μm. Before laying the titanium alloy powder, the titanium alloy powder is dried and sieved to remove impurities and agglomerated particles. S2. Powder laying The pre-treated titanium alloy powder is laid on the workbench of the selective laser melting and sintering equipment. The laying thickness is controlled at 50μm to ensure a uniform powder layer and avoid local accumulation or vacancies. S3. Laser Melting and Sintering A high-power fiber laser is used to scan and sinter the laid powder layer. The laser power is 100W and the scanning speed is 500mm / s. The laser selectively melts according to the preset mechanical superstructure model path, so that the powder particles fuse with each other to form a solid structural layer. S4. Layer by layer After one layer is sintered, the workbench descends to a height that matches the set layer thickness. The powder spreading device then evenly spreads the titanium alloy powder on the surface of the sintered structural layer, repeating the laser melting and sintering process in step 4. This cycle repeats until a complete SC+FCC mechanical superstructure material body is gradually formed. S5. Post-processing The unsintered powder attached to the surface of the material body is removed by high-pressure air blowing and vibration screening. The material body is annealed to eliminate internal stress at 600°C and the holding time is 1 hour. Finally, the material is precisely processed to obtain the support energy absorption layer 2. The microstructure of the support energy absorption layer 2 is as follows: Figure 3 shown.

[0019] The method for preparing an explosion-proof component comprises the following steps: S1.Surface treatment The bottom surface of the crushing energy absorbing layer 1, the upper and lower surfaces of the supporting energy absorbing layer 2, and the top surface of the debris protection layer 3 are sandblasted to remove the surface oxide layer and impurities, and the roughness is controlled at Ra1.6μm; S2. Gluing and lamination Evenly coat the upper surface of the supporting energy absorbing layer 2 with epoxy resin adhesive to a thickness of 0.2 mm, align the bottom surface of the crushing energy absorbing layer 1 with the upper surface of the supporting energy absorbing layer 2, apply a pressure of 5 MPa, and preliminarily cure at room temperature for 1 hour; S3. Secondary gluing and lamination The same adhesive is coated on the lower surface of the supporting energy-absorbing layer 2 with a thickness of 0.2 mm. The top surface of the fragment protection layer 3 is aligned with the lower surface of the supporting energy-absorbing layer 2, a pressure of 5 MPa is applied, and the mixture is cured at 60°C for 4 hours to obtain a complete explosion-proof assembly.

[0020] Explosion-proof component testing for 100g TNT equivalent Component structure: 14mm boron carbide ceramic (crushing energy absorption layer 1) + 6mm SC+FCC mechanical superstructure material (supporting energy absorption layer 2) + 4mm ultra-high molecular weight polyethylene fiber composite material (debris protection layer 3), size 100mm×100mm; Test device: A plane wave generator was used to simulate the explosion environment. Foil-shaped H-type manganese-copper piezoresistive sensors were placed on the ceramic explosion-facing surface and the back of the fragment protection layer to measure the impact pressure. Test results: The maximum pressure on the explosion surface is 27.59 GPa (at 10.021 μs); The maximum pressure on the back side is 7.712 GPa (at 18.900 μs); The pressure decay rate is (27.59-7.712) / 27.59×100%=72.05%, which verifies the efficient energy absorption performance of the component; After-effect observation: After the explosion, the ceramic layer was shattered, the mechanical superstructure layer was deformed and disintegrated, the fragment protection layer completely intercepted the fragments, and there was no penetration damage to the after-effect armor steel back explosion surface.

[0021] This embodiment shows that the explosion-proof component can effectively attenuate the explosion shock wave and intercept fragments while being lightweight, thus meeting the protection requirements of the mine-proof and ambush-proof vehicle.

[0022] The test device is Figure 2 The plane wave generator shown in the figure has a charge of 100g of TNT. Foil-shaped H-shaped manganese-copper piezoresistive sensors are placed between the ceramic and the plane wave generator, and between the composite material and the armor steel after-effect plate, respectively, to measure the impact pressure on the front and rear blast surfaces.

[0023] Figure 4 The pressure data of the ceramic and plane wave generator are as follows. The pressure on the sample's explosion surface is the highest at 10.021μs. The pressure value of 27.59GPa at this moment is taken as the explosion surface pressure of the composite armor sample in this test. Figure 5 This is the pressure data between the composite material and the armor steel after-effect plate. The maximum pressure is 7.712GPa at 18.900μs on the back explosion surface. Figure 6 These are photos of the front and back blast surfaces of the armor steel after the test.

[0024] The test results show that the composite structure of the invention has a surface density of 48kg / m 2 Under the conditions of , the impact pressure generated by 100gTNT explosive was attenuated by 72.05%.

[0025] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. An explosion-proof component based on ceramic and mechanical superstructure materials, characterized by: include: A crushing energy absorbing layer (1), wherein the crushing energy absorbing layer (1) is made of boron carbide ceramics and is used to reflect and refract the refracted waves of the explosion surface to dissipate the impact energy; A supporting energy-absorbing layer (2), wherein the supporting energy-absorbing layer (2) absorbs the impact energy after the ceramic is refracted by deforming itself; The fragment protection layer (3) is an ultra-high molecular weight polyethylene fiber composite material, and is used to intercept ceramic fragments that break the energy absorbing layer (1) and fragments that support the energy absorbing layer (2).

2. The explosion-proof component based on ceramic and mechanical superstructure materials according to claim 1, characterized in that: The preparation method of the supporting energy absorbing layer (2) is as follows: S1. Raw material preparation Prepare a raw material containing 90% titanium, 6% aluminum, and 4% vanadium by weight, and prepare the raw material into a titanium alloy powder, wherein the particle size of the titanium alloy powder is 15-53 μm; S2. Powder laying The pre-treated titanium alloy powder is laid on the workbench of the selective laser melting and sintering equipment. The laying thickness is controlled at 50-100μm to ensure a uniform powder layer and avoid local accumulation or vacancies. S3. Laser Melting and Sintering Use a high-power fiber laser to scan and sinter the laid powder layer. The laser selectively melts according to the preset mechanical superstructure model path, so that the powder particles fuse together to form a solid structural layer. S4. Layer by layer After one layer is sintered, the workbench descends to a height corresponding to the set layer thickness, which is consistent with the laying thickness. Then, the powder spreading device again evenly spreads the titanium alloy powder on the surface of the sintered structural layer, repeating the laser melting and sintering process in step 4. This cycle is repeated to gradually accumulate and form a complete SC+FCC mechanical superstructure material blank. S5. Post-processing The unsintered powder attached to the surface of the material body is removed by high-pressure air blowing and vibration screening; the material body is annealed to eliminate internal stress at an annealing temperature of 600-800°C and a holding time of 1-2 hours; finally, the material is precisely processed in terms of external dimensions to obtain a supporting energy-absorbing layer (2).

3. The explosion-proof component based on ceramic and mechanical superstructure materials according to claim 1, characterized in that: The method for preparing the explosion-proof component comprises the following steps: S1.Surface treatment The bottom surface of the crushing energy absorbing layer (1), the upper and lower surfaces of the supporting energy absorbing layer (2), and the top surface of the debris protection layer (3) are sandblasted to remove the surface oxide layer and impurities, and the roughness is controlled within Ra1.6-3.2μm; S2. Gluing and lamination Evenly coat the upper surface of the supporting energy absorbing layer (2) with epoxy resin adhesive to a thickness of 0.2-0.5 mm, align the bottom surface of the crushing energy absorbing layer (1) with the upper surface of the supporting energy absorbing layer (2), apply a pressure of 5-10 MPa, and preliminarily cure at room temperature for 1-2 hours; S3. Secondary gluing and lamination The same adhesive is coated on the lower surface of the supporting energy absorbing layer (2) with a thickness of 0.2-0.5 mm, the top surface of the fragment protection layer (3) is aligned and bonded to the lower surface of the supporting energy absorbing layer (2), a pressure of 5-10 MPa is applied, and the mixture is cured at 60-80° C. for 4-6 hours to obtain a complete explosion-proof assembly.

4. The explosion-proof component based on ceramic and mechanical superstructure materials according to claim 2, characterized in that: Before the titanium alloy powder is laid, the titanium alloy powder is dried and sieved to remove impurities and agglomerated particles.

5. The explosion-proof component based on ceramic and mechanical superstructure materials according to claim 2, characterized in that: The laser power of the laser melting is 100-200W, and the scanning speed is 500-1000mm / s.

Citation Information

Patent Citations

  • Layer structure of bulletproof armor module

    CN103822541A

  • Lightweight bulletproof and antiknock multiphase composite armor material based on high-toughness heterogeneous interface layer

    CN115127398A

  • Lightweight armor and preparation method thereof

    CN115847937A

  • Composite shock-wave-resistant fragment laminate

    CN117601517A

  • Multi-level near-field explosion protection structure

    CN117989949A